Recent Trends of Practical Theology in Finland: The Research Field of Practical Theology and Religious Education from the Perspective of Paradigms and the Operating Environment in the First Decades of the 21st Century at the University of Helsinki - Räsänen, Antti (International journal of practical theology, 2024)
This paper explores historical and recent developments in Finnish Practical Theology and Religious Education. It reconstructs the operating environment under which PT and RE exist in Finland, i. e. its political, economic, and cultural circumstances. To this end, the authors highlight developments such as the transition from a rural-centric to an urban society, the impact of political left-wing ideology, and the impact of Finland’s joining the European Union. Through an analysis of dissertation research at Helsinki University, the paper provides an overview of current topics of research in Finnish PT. The authors concluds with insights into likely future developments in the 21st century.